Digital Campaign Strategies to Engage Consumer Multiculturation: Pakistani Gen Z Responses - Pranajaya, Ade; Rashid, Sara (ACADEMIA International Journal for Social Sciences, 2025)
This study explores how Indonesia’s digital campaigns, which include engaging content and social media activities, influence Pakistani Generation Z consumers’ multiculturation using the Cross-Cultural Understanding (CCU) framework. Using consumer multiculturation theory and the Stimulus–Organism–Response (S–O–R) model, it describes CCU as a key process connecting digitally driven diplomatic and marketing stimuli to how young people interpret and incorporate foreign cultural cues into their consumption habits. Focusing on Indonesia’s digital outreach in Pakistan—such as cultural, tourism, and culinary storytelling; embassy and consulate social media channels; and platform-based campaigns—this study tests a streamlined structural model where digital content and social media initiatives predict CCU among Pakistani Gen Z. PLS-SEM analysis reveals that both digital content and social media campaigns positively and significantly influence CCU, with campaign efforts exerting a notably stronger effect. The model explains a significant portion of the variance in CCU (R²≈0.674). Overall, the research indicates that CCU should be seen not only as a measure of visibility but as the main point of conversion in consumer multiculturation. It reinterprets digital campaigns as culturally driven learning platforms that deliver intercultural knowledge through relatable narratives and promote dialogue-driven meaning-making via platform-specific engagement. The study provides practical design principles for Indonesia’s digital nation branding, applicable to similar countries, especially in Muslim-majority, youth-centered markets.